2011
DOI: 10.1371/journal.ppat.1002397
|View full text |Cite
|
Sign up to set email alerts
|

The Splicing Factor Proline-Glutamine Rich (SFPQ/PSF) Is Involved in Influenza Virus Transcription

Abstract: The influenza A virus RNA polymerase is a heterotrimeric complex responsible for viral genome transcription and replication in the nucleus of infected cells. We recently carried out a proteomic analysis of purified polymerase expressed in human cells and identified a number of polymerase-associated cellular proteins. Here we characterise the role of one such host factors, SFPQ/PSF, during virus infection. Down-regulation of SFPQ/PSF by silencing with two independent siRNAs reduced the virus yield by 2–5 log in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 77 publications
0
62
0
Order By: Relevance
“…Furthermore, cyclin T1/CDK9 is proposed to recruit vRNP to hyperphosphorylated Pol II for cap snatching and to facilitate viral mRNA transcription (29). Additionally, splicing factor proline-glutamine rich (SFPQ/PSF) has been found to increase the efficiency of viral mRNA polyadenylation (30). In this study, we identified RRP1B as another important host factor for influenza virus transcription.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, cyclin T1/CDK9 is proposed to recruit vRNP to hyperphosphorylated Pol II for cap snatching and to facilitate viral mRNA transcription (29). Additionally, splicing factor proline-glutamine rich (SFPQ/PSF) has been found to increase the efficiency of viral mRNA polyadenylation (30). In this study, we identified RRP1B as another important host factor for influenza virus transcription.…”
Section: Discussionmentioning
confidence: 86%
“…In agreement with this transcriptional association, interaction of the viral polymerase with host cell transcription-related factors has been reported, among which the interaction with the largest subunit of the RNAP II (11) should be emphasized. Other transcription-related factors found to interact with the viral polymerase are Erb-B3 binding protein 1 (Ebp-1) (12), which represses transcription of cell cycle genes regulated by E2F transcription factors (13); DDX5 protein (14), a transcription coactivator that may play a role in transcription initiation (15); SFPQ/PSF factor (14), which stimulates pre-mRNA processing (16) and is essential for influenza virus transcription increasing the efficiency of viral mRNA polyadenylation (17); and hCLE, a positive modulator of the RNAP II (18,19) which is required for influenza virus replication (20).…”
mentioning
confidence: 99%
“…Additionally, the most significantly enriched functional category in the emerging concepts was uniquely identified by INCATome ("Viral life cycle"). Several lines of evidence have been reported linking PSF and viral replication, gene expression, and reproductivity of HIV, influenza, and hepatitis delta viruses (Zolotukhin et al 2003;Greco-Stewart et al 2006;Landeras-Bueno et al 2011;Kula et al 2013). Finally, albeit INCATome yielded only four novel concepts, these have the specificity of not representing either responses to stimulus or developmental processes unlike all other novel concepts identified.…”
Section: New Biological Inferences Discovered With Incatomementioning
confidence: 98%